Penerapan Metode Problem Based Learning Untuk Meningkatkan Hasil Belajar Siswa Sekolah Dasar - Abdul Rozi (Jurnal Indonesia Pendidikan Profesi Guru, 2025)
Background: This study was conducted to evaluate the application of Problem-Based Learning (PBL) in Islamic Education at SD Negeri 149 Palembang, specifically on the subject of Asmaul Husna. Objective: The study aimed to determine the effectiveness of PBL in improving student learning outcomes in this subject. Method: The research used a Classroom Action Research (CAR) design, which was implemented in three cycles. Data collection was conducted through observations and tests, and the data were analyzed using quantitative methods to assess the average test scores, learning completeness, and student achievement. Result; The results showed that PBL was effective in improving student learning outcomes. In the first cycle, learning completeness reached 68%, which increased to 85% in the second cycle and 94% in the third cycle. This improvement indicates that PBL can enhance students' understanding and involvement in learning. Conclusion; The application of PBL proved to be effective in improving student learning outcomes at SD Negeri 149 Palembang, particularly in the Asmaul Husna material. PBL succeeded in increasing student engagement, encouraging them to think critically and apply the values they learned in their daily lives. Contribution: This study contributes to the development of PBL as an alternative method for active and applied learning at the elementary school level. These findings can serve as a reference for teachers to implement the PBL method to improve the quality of education and student learning outcomes in various schools.